Intellectual potential in the system of marketing of Innovation - ZRYBNIEVA, IRYNA; Бабух, Ілона (НАНУ ДУ "Інститут досліджень науково-технічного потенціалу та історії науки ім. Г.М. Доброва НАН України", 2018)
The company, based on the use of marketing of innovations in the development of an intelligent product, must take into account the complex factors of lateral marketing, which generates creative, non-standard ideas, implements them in unique, non-standard solutions. Human talent is the main strategic resource of lateral marketing, which means that the commercial structure requires the presence of intellectual potential, that is, in the personified marketing service there are a system of knowledge, professional competence, the desire for a new, quick reaction, communicability, ability to quench conflicts, optimism, that is, knowledge management mechanisms, creative thinking of workers. These mechanisms, when implementing innovative strategies in the field of commerce, help to successfully use marketing tools designed for competitive.
Keywords: marketing of innovations in commerce; lateral marketing; human talent; intellectual potential